Дослідження фітобіоти (ІІ –й відкритий з’їзд фітобіологів Херсонщини, Херсон, 15 травня 2008 р.) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Дослідження фітобіоти (ІІ –й відкритий з’їзд фітобіологів Херсонщини, Херсон, 15 травня 2008 р.)